2022
DOI: 10.1186/s12883-022-02843-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of visual scanning exercises in addition to task specific approach on balance and activities of daily livings in post stroke patients with eye movement disorders: a randomized controlled trial

Abstract: Background Impaired vision is one of the commonest and most disabling consequence following stroke. Among all visual impairments, eye movement disorders are found in 70% of stroke patients which include nystagmus, strabismus, gaze palsies, disconjugate eye movements and cranial nerve palsies. They have a wide ranging impact on balance and activities of daily livings by creating difficulties in maintaining normal alignment and appropriate movement of eyes. The purpose of this study was to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…All participants had a history of diagnosed stroke and were aged between 30 and 77 years. One study examined participants with a mean age of 30.9–39.8 years [ 56 ], 14 studies of 52.5–62.6 years [ 55 , 58 , 59 , 76 , 78 , 80 , 82 84 , 87 , 88 , 90 , 92 , 94 ], six of 64.0–67.6 years [ 57 , 77 , 81 , 85 , 86 , 91 ], and three of 70.7–77.7 years [ 79 , 89 , 93 ]. A total of 357 women and 532 men were studied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants had a history of diagnosed stroke and were aged between 30 and 77 years. One study examined participants with a mean age of 30.9–39.8 years [ 56 ], 14 studies of 52.5–62.6 years [ 55 , 58 , 59 , 76 , 78 , 80 , 82 84 , 87 , 88 , 90 , 92 , 94 ], six of 64.0–67.6 years [ 57 , 77 , 81 , 85 , 86 , 91 ], and three of 70.7–77.7 years [ 79 , 89 , 93 ]. A total of 357 women and 532 men were studied.…”
Section: Resultsmentioning
confidence: 99%
“…The localisation was indicated by five studies with right hemisphere [ 58 , 78 , 81 , 86 , 94 ], six with various [ 55 , 57 , 59 , 77 , 87 , 90 ], while all others did not provide any information. The main symptoms of the participants indicated eleven studies with cognitive dysfunction [ 55 57 , 59 , 78 , 79 , 82 , 83 , 86 – 88 ], five with motor dysfunction [ 58 , 77 , 90 , 92 , 94 ], three with visual disorders [ 80 , 81 , 89 ], and five did not provide any information [ 76 , 84 , 85 , 91 , 93 ]. For the time since stroke event, one study gave no indication [ 89 ], two generally less than 3 months [ 55 , 90 ], two from 3 to 6 months [ 56 , 80 ], three less than 6 months [ 57 , 59 , 87 ], two 0.5–0.6 months [ 58 , 86 ], seven 1.0–3.2 months [ 77 , 81 , 85 , 88 , 91 , 93 , 94 ], two 4.0–4.9 months [ 79 , 92 ], one more than 6 months [ 84 ], and four 8.3–20.8 months [ 76 , 78 , 82 , 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…1 Intern, Department of Neurophysiotherapy, Ravi Nair Physiotherapy College, DMIHER (DU), Sawangi, Wardha, Maharashtra, India-442001 2 Assistant Professor, Department of Neurophysiotherapy, Ravi Nair brain (Thompson et al, 2022). Neuroectodermal choroid plexus tumors are an uncommon kind of cerebral malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to excise CPP due to its highly vascular nature but survival rate and success rate of this operation are pretty good. Physiotherapy was started on next dayBatool et al, (2022) carried out research which showed effect of visual scanning exercise on balance and stability. Study was carried on 64 individuals divided into experimental group and control group.…”
mentioning
confidence: 99%
See 1 more Smart Citation